Study on factors leading causes of infertility among couple in Kathmandu valley, Nepal. - Neupane, Pratima (2014)
ABSTRACT: The problem of infertility has not given due attention because it is not a life-threatening condition with invisible losses, and it consequences are manifold. Infertility is defined as the inability of a couple to conceive after twelve months of regular, unprotected intercourse. There are two types of infertility primary and secondary. Couples with primary infertility have never been able to conceive. While on the other hand secondary infertility is difficulty conceiving after already having conceived and either carried the pregnancy to term or had a miscarriage. However infertility is a clinical presentation and not a disease. The objective of the study is to find out the factors contributing male infertility, to find out the factors contributing female infertility, to assess the present health status of male and female, to evaluate the primary and secondary cases. This descriptive study had been carried out in Kathmandu metropolitan city, Nepal. 165 married couple (male and female) with infertility problem availing the infertility treatment was selected on first come first serve basic sampling methods from infertility treatment center. The results of the study shows that 44.4% male belongs to the age group 31 to 35 years and 51% female were at the age group 26 to 30 years. Majority 44.8% of the male were married at 25 to 29 years of age followed by 37.8% female were married at the age 21 to 25 years of age. More than 67% men respondents were executive officer and their duration of working hours is 9 to 12 hours. Forty three percentage of female reported they were house wives. Drinking and smoking habit was higher in male as compare to female. six per cent husband had Family history of infertility. Main causes of infertility in male includes history of mumps orchitis 16.2%, azoospermia 19%, and 11.1% had severe oligospermia. According to health status majority 19% male had high blood pressure problem, 62.5% males had history of hydrocele surgery, 14% male were suffered with high grate fever in last 6 month and high BMI found in female 9% and 3% male were in pre obese class I. Causes of infertility in female includes ovulation disorder 47.2%, Thyroid disease 23.8%, UTI 20.4%, ovarian cyst 43.8%, vaginal fungal infection 19.6%, TOURCH positive 18%, history of ectopic pregnancy surgery 26.9%, fibroid surgery 23.1% and miscarriages 32.7%. In this study the ratio of primary infertility is 66.7% and the secondary sterility is 33.3%. Fifty per cent of the primary infertile couples were treated with IUI. Contributing factors of infertility in male were more than in female. Health status of wives contributes for infertility in female is more than in males. More than half of the couple had primary infertility problem and half of the primary infertile couple were treated with IUI.